Comparison of Glioblastoma Outcomes in Two Geographically and Ethnically Distinct Patient Populations in Disparate Health Care Systems - Mirza, Farhan A.; Baqai, Muhammad Waqas S.; Hani, Ummey; Hulou, Maher; Shamim, Muhammad Shahzad; Enam, Syed Ather; Pittman, Thomas (Asian Journal of Neurosurgery, 2022)
Introduction Variations in glioblastoma (GBM) outcomes between geographically and ethnically distinct patient populations has been rarely studied. To explore the possible similarities and differences, we performed a comparative analysis of GBM patients at the University of Kentucky (UK) in the United States and the Aga Khan University Hospital (AKUH) in Pakistan.Methods A retrospective review was conducted of consecutive patients who underwent surgery for GBM between January 2013 and December 2016 at UK, and July 2014 and December 2017 at AKUH. Patients with recurrent or multifocal disease on presentation and those who underwent only a biopsy were excluded. SPSS (v.25 IBM, Armonk, New York, United States) was used to collect and analyze data.Results Eighty-six patients at UK (mean age: 58.8 years; 37 [43%] < 60 years and 49 [57%] > 60 years) and 38 patients at AKUH (mean age: 49.1 years; 30 (79%) < 60 years and 8 (21%) > 60 years) with confirmed GBM were studied. At UK, median overall survival (OS) was 11.5 (95% confidence interval [CI]: 8.9–14) months, while at AKUH, median OS was 18 (95% CI: 13.9–22) months (p = 0.002). With gross-total resection (GTR), median OS at UK was 16 (95% CI: 9.5–22.4) months, whereas at AKUH, it was 24 (95% CI: 17.6–30.3) months (p = 0.011).Conclusion Median OS at UK was consistent with U.S. data but was noted to be longer at AKUH, likely due to a younger patient cohort and higher preoperative Karnofsky's performance scale (KPS). GTR, particularly in patients younger than 60 years of age and a higher preoperative KPS had a significant positive impact on OS and progression-free survival (PFS) at both institutions.
Keywords: glioma; glioblastoma; survival; population heterogeneity; health care system; Pakistan